2022
DOI: 10.3389/fendo.2021.794568
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese Patent Medicine JiaYanKangTai Alleviates Inflammatory Lesions of Experimental Autoimmune Thyroiditis by Regulating Interleukin-17 Signaling

Abstract: ObjectiveThis study was aimed to investigate the effects of JiaYanKangTai (JYKT) on regulating interleukin-17 (IL-17) signaling in rats with autoimmune thyroiditis.MethodsLewis rats were administrated with JYKT for eight weeks after a seven-week subcutaneous injection of thyroglobulin with adjuvant and feeding iodine water. Ultrasonography was performed and total volume of thyroid was calculated. The expressions of autoantibodies and hormones were detected. Morphological changes of thyroid were observed. Metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In addition, the down-regulation of RAC1 was linked with ERK1/2 pathways which favor the protection of thyrocyte cells [ 38 ] and other cell types [ 23 ] from inflammation-induced apoptosis. A recent study demonstrated that a Chinese patent medicine decreased both levels of TgAb and TPOAb, and alleviated lymphocytic infiltration by regulating expressions of p-ERK1/2 in a rat model [ 39 ], which further highlighted the crucial role of ERK1/2 signals in the HT progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the down-regulation of RAC1 was linked with ERK1/2 pathways which favor the protection of thyrocyte cells [ 38 ] and other cell types [ 23 ] from inflammation-induced apoptosis. A recent study demonstrated that a Chinese patent medicine decreased both levels of TgAb and TPOAb, and alleviated lymphocytic infiltration by regulating expressions of p-ERK1/2 in a rat model [ 39 ], which further highlighted the crucial role of ERK1/2 signals in the HT progression.…”
Section: Discussionmentioning
confidence: 99%